2017
DOI: 10.1051/epjconf/201715703003
|View full text |Cite
|
Sign up to set email alerts
|

Ray Tracing Study on Top ECCD Launch in KSTAR

Abstract: Abstract. The current drive efficiency of electron cyclotron (EC) wave is typically low compared with other RF and neutral beam heating system in tokamak. It is known that EC current drive by outboard launch suffers from low current drive efficiency due to electron trapping. However, the heating and current drive by EC wave is being regarded as a strong candidate for DEMO reactor due to the simplicity of the launcher, none of its interaction with plasma, and no coupling issue at the plasma edge. Also, off-axis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 2 publications
(3 reference statements)
0
4
0
Order By: Relevance
“…In previous calculation [2], the vertical top launch of 140 GHz X2 wave with B0 = 2 T at the magnetic axis shows strong sensitivity of wave trajectory on both azimuthal and polar angles of injection. In this paper, the fundamental O-mode of 105 GHz wave is used for the new vertical top launch study with the toroidal magnetic field of 3 T at the magnetic axis (R0 = 1.8 m).…”
Section: Up-shift Top Launch Of 105 Ghz O1 Wavementioning
confidence: 78%
See 1 more Smart Citation
“…In previous calculation [2], the vertical top launch of 140 GHz X2 wave with B0 = 2 T at the magnetic axis shows strong sensitivity of wave trajectory on both azimuthal and polar angles of injection. In this paper, the fundamental O-mode of 105 GHz wave is used for the new vertical top launch study with the toroidal magnetic field of 3 T at the magnetic axis (R0 = 1.8 m).…”
Section: Up-shift Top Launch Of 105 Ghz O1 Wavementioning
confidence: 78%
“…In the KSTAR ECRH system upgrade plan, we will install four 105/140 GHz gyrotrons and two 170 GHz gyrotrons with 1 MW output power each. In the pre-liminary study [2], vertical top launch of electron cyclotron (EC) wave shows improvement in EC current drive (ECCD) efficiency with broad ECCD profile peaked off-axis. It is understood that the vertical top launch of EC wave enables nearly vertical trajectories on the low field side from the cold resonance, called "up-shift" resonance.…”
Section: Introductionmentioning
confidence: 99%
“…From this point of view, it is necessary to use the additional EC-wave launchers to control the TAEs and the tearing modes simultaneously. Since the efficiency of the off-axis current drive is not so high when launching from the low-field side due to electron trapping, vertical launching of the ECCD from the top-port [81] planned on KSTAR will be beneficial to the control of the TAEs with minimizing tearing mode activities. In addition, upcoming off-axis NBI is expected to be beneficial to examine the AE suppressions in which the radial location of the maximum fast-ion pressure gradient is outside of the core region.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…This leads to a predicted increase in ECCD efficiency as originally discussed for ω < Ω ce launch of fundamental X-mode without trapping effects [12,13] but reported here for the reactor-relevant scheme of ω > 2Ω ce launch of second-harmonic X-mode (isomorphic to fundamental O-mode). Other studies have shown that moving the EC launch location from the outside midplane to the upper portion of the vessel greatly increases the ECCD efficiency [14][15][16], while the practical benefits accrued by top launch ECCD have been pointed out by simulations for FNSF-AT showing a greater than 50% improvement in off-axis ECCD using top launch compared to the conventional outside launch [17] and by survey studies for DEMO [18], KSTAR [19], and CFETR [20]. These improvements in current drive efficiency that accrue from top launch can be crucial in making DEMO and FNSF-AT practical.…”
mentioning
confidence: 99%